2019
DOI: 10.1016/j.jhin.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of participation in a surgical site infection surveillance network: results from a large international cohort study

Abstract: Impact of participation in a surgical site infection surveillance network: results from a large international cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 25 publications
0
39
0
3
Order By: Relevance
“…Checking the relevance of each singular case is more suitable for a local survey (i.e., single-hospital or regional network) than for a national survey, as the absence of uniform national guidelines may lose some relevant amount of HDF information to poor compliance. Indeed, surveys are increasingly being performed in Italian regions and university hospitals [1,6,33], while systematic surveillance networks are being tested on an international scale [13]. Two reviews and one retrospective observational study found OIDRI treatment success rates to vary between 57 and 88% [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Checking the relevance of each singular case is more suitable for a local survey (i.e., single-hospital or regional network) than for a national survey, as the absence of uniform national guidelines may lose some relevant amount of HDF information to poor compliance. Indeed, surveys are increasingly being performed in Italian regions and university hospitals [1,6,33], while systematic surveillance networks are being tested on an international scale [13]. Two reviews and one retrospective observational study found OIDRI treatment success rates to vary between 57 and 88% [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Although estimating HAI incidence, complications, and attributable mortality is challenging [12], evidence suggests that systematic surveillance can help to prevent and reduce their burden [13][14][15]. These data highlight the need to identify which patients, procedures, settings and devices are most at risk.…”
Section: Introductionmentioning
confidence: 99%
“…7 The use of surveillance to measure the risk of surgical site infection and feedback of results to surgeons has been shown to be effective in reducing the risk of infection. [8][9][10] However, surveillance of surgical site infection is resource intensive and studies to assess its cost-benefit have not been conducted. The Surgical Site Infection Surveillance Service at Public Health England provides national coordination for surgical site infection surveillance for hospitals in England.…”
Section: Introductionmentioning
confidence: 99%
“…In a large‐scale study conducted by the National Healthcare Safety Network, which included 850 thousand general surgeries from across United States, the incidence of SSI was 1.9% . Surveillance of SSI rates and adherence to protocols designed to minimize risk have been shown to decrease SSI rates in high‐income countries . Few short‐term surgical missions report complications rates .…”
Section: Introductionmentioning
confidence: 99%